1999
DOI: 10.1136/oem.56.8.527
|View full text |Cite
|
Sign up to set email alerts
|

Bronchoalveolar inflammation after exposure to diesel exhaust: comparison between unfiltered and particle trap filtered exhaust.

Abstract: Objectives-Air pollution particulates have been identified as having adverse eVects on respiratory health. The present study was undertaken to further clarify the eVects of diesel exhaust on bronchoalveolar cells and soluble components in normal healthy subjects. The study was also designed to evaluate whether a ceramic particle trap at the end of the tail pipe, from an idling engine, would reduce indices of airway inflammation. Methods-The study comprised three exposures in all 10 healthy never smoking subjec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
91
2
3

Year Published

2000
2000
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 146 publications
(100 citation statements)
references
References 22 publications
4
91
2
3
Order By: Relevance
“…Numerous epidemiological studies have documented a detrimental relationship between exposure to particulate matter in urban air pollution and cardiopulmonary morbidity and mortality with both short-and long-term exposure [1][2][3][4][5]. Although the mechanism by which exposure to particles in urban air induces adverse cardiopulmonary effects remains unclear, several studies from the present authors' laboratory and others support a mechanism in which exposure to fine particles promotes inflammation in the lung [6][7][8][9][10][11] via activation of alveolar macrophages and lung epithelial cells [12][13][14][15][16]. Such exposure is also associated with a systemic inflammatory response [17][18][19][20], which in turn is associated with an increased presence of several cytokines (interleukin (IL)-6, IL-1b) in the bloodstream [21] as well as increased production and release of polymorphonuclear leukocytes (PMN) and monocytes from the bone marrow [17][18][19][20].…”
mentioning
confidence: 57%
“…Numerous epidemiological studies have documented a detrimental relationship between exposure to particulate matter in urban air pollution and cardiopulmonary morbidity and mortality with both short-and long-term exposure [1][2][3][4][5]. Although the mechanism by which exposure to particles in urban air induces adverse cardiopulmonary effects remains unclear, several studies from the present authors' laboratory and others support a mechanism in which exposure to fine particles promotes inflammation in the lung [6][7][8][9][10][11] via activation of alveolar macrophages and lung epithelial cells [12][13][14][15][16]. Such exposure is also associated with a systemic inflammatory response [17][18][19][20], which in turn is associated with an increased presence of several cytokines (interleukin (IL)-6, IL-1b) in the bloodstream [21] as well as increased production and release of polymorphonuclear leukocytes (PMN) and monocytes from the bone marrow [17][18][19][20].…”
mentioning
confidence: 57%
“…The presence of a neutrophilic inflammation has further been reported in BAL at 18 h after DE exposure [14,15]. Although the human data on the time course of the neutrophilic response to DE is limited, the results from these studies seem to suggest the peak response to occur sometime between 6 and 18 h following exposure.…”
Section: Discussionmentioning
confidence: 92%
“…In working environments, exposure to DE has been associated with various symptoms related to the eyes and airways [10±12]. In experimental chamber studies, DE has been shown to cause airway symptoms [13] and to induce an acute inflammatory response in human airways as reflected in bronchoalveolar lavage [14,15] and bronchial biopsy [16] samples. Further, local nasal challenge with DE particles has been reported to enhance immunoglobulin E production in the nose [17] and to cause an increased cytokine response in the nose of allergic subjects [18].…”
mentioning
confidence: 99%
“…Numerous environmental pollutants can provoke an inflammatory response in patients with COPD (36)(37)(38). Importantly, epidemiologic studies have confirmed increased respiratory symptoms and mortality during times of increased air pollution (39)(40)(41).…”
Section: Pathogenesismentioning
confidence: 99%